PONDOK PESANTREN DALAM PENGEMBANGAN MASYARAKAT DAN PENDIDIKAN: (Studi Kasus pada Pondok Pesantren Ibnul Amin, Pamangkih, Labuan Amas Utara, Kabupaten Hulu Sungai Tengah Kalimantan Selatan) - Ubaidillah Ubaidillah (Cross-border, 2021)
This study aims to determine the role of the Islamic boarding school Ibnul Amin in community development and education. This research is descriptive-qualitative research. Data was collected by participating in observations, interviews, and documentation. There are three things that are important to be described in this study, namely the role of the Ibnul Amin Islamic Boarding School in Community Development in the field of education in the form of increasing community human resources, in this case teachers, leaders, and education actors by means of khidmah tarbawiyah; services through training of educators, teacher training in Arabic, and teacher training in the field of Mathematics and Natural Sciences. Efforts in this field, although not maximized, have at least contributed to the development of society. As for the social sector, the Ibnul Amin Islamic Boarding School seeks the realization of Poskestren, Kopmastren, Development in the Economy. Empowerment of Small and Medium Enterprises for the community. In the field of Islamic da'wah, the emphasis is on religious issues and social relations between each other, through religious lectures, religious consultations, and enlivening the symbols of Islam and no less important is da'wah providing direct examples to the community in terms of doing good deeds, doing real work. in order to achieve the real purpose of life. The author considers that the Ibnul Amin Islamic Boarding School still needs to be seen from all aspects, both organizational aspects, and work programs that have been and will be carried out, so that it can be categorized that the Ibnul Amin Islamic Boarding School really carries out its functions and duties for the betterment of the Barabai community as a whole. Specifically and Indonesia in general.